A Palpable Painless Axillary Mass as the Clinical Manifestation of Castleman’s Disease in a Patient with Hepatitis C Disease - Athanasia K. Papazafiropoulou; Angeliki M. Angelidi; Antonis A. Kousoulis; Georgios Christofilidis; Chariklia Sagia; Liountmila Kaftanidou; Kassiani Manoloudaki; Aikaterini Tsavari; Georgios Kranidiotis; Alexandros Kamaratos; Andreas Melidonis (Case Reports in Medicine)
Introduction. Castleman’s disease (CD) is a rare lymphoproliferative disorder. CD is divided into two clinical subtypes: the most common unicentric and the less usual multicentric subtype. The majority of unicentric CD affects the mediastinum, while neck, abdomen, and axilla are less common locations. Case Presentation. Herein, we describe a rare case of unicentric CD in the right axilla in a 36-year-old white male with a medical history of hepatitis C virus infection admitted to our hospital due to palpation of a painless mass in the right axilla. Complete excision of the lesion was performed and, one year after the diagnosis, patient was free of the disease. Conclusions. Although infrequent, it is important to include CD in the differential diagnosis when evaluating axillary lymphadenopathy particularly in young patients with a low-grade inflammation process and chronic disease even in the absence of an abnormal blood picture or organomegaly.